2016
DOI: 10.1016/j.foodchem.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds of ‘Galega Vulgar’ and ‘Cobrançosa’ olive oils along early ripening stages

Abstract: In this study, the lipophilic and hydrophilic phenol composition of virgin olive oils (VOO) obtained from olives from two of the most important Portuguese cultivars ('Galega Vulgar' and 'Cobrançosa'), harvested at different ripening stages and under two irrigation schemes (rain fed and irrigated), was evaluated. Phenolic alcohols (hydroxytyrosol and tyrosol), phenolic acids and derivatives and flavonoids (luteolin and apigenin), as well as tocopherols were quantified. Lipophilic (>300mgkg(-1)) and hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 36 publications
11
41
0
5
Order By: Relevance
“…Verdeal was the poorest, with 140 mg/kg in 2016 and 172 mg/kg in 2017. These results agree in general with the ones obtained for different cultivars in different parts of the world, with average amounts varying from 50 to 500 mg/kg of olive oil, and also for the Portuguese cultivars (Galega Vulgar and Cobrançosa) (Peres et al, 2016) suggesting that the amount of vitamin E highly depends on the olive cultivar (Beltrán et al, 2010;Reboredo-Rodríguez et al, 2016;Tura et al, 2007) but also influenced by other factors like maturation process and agro-climatic conditions. In the present work, the severe drought observed during the year 2017 (data not shown) probably promoted the synthesis of these antioxidants, perhaps as a protection of the plant against the increased environmental stress (Beltrán et al, 2005).…”
Section: Quality and Physicochemical Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…Verdeal was the poorest, with 140 mg/kg in 2016 and 172 mg/kg in 2017. These results agree in general with the ones obtained for different cultivars in different parts of the world, with average amounts varying from 50 to 500 mg/kg of olive oil, and also for the Portuguese cultivars (Galega Vulgar and Cobrançosa) (Peres et al, 2016) suggesting that the amount of vitamin E highly depends on the olive cultivar (Beltrán et al, 2010;Reboredo-Rodríguez et al, 2016;Tura et al, 2007) but also influenced by other factors like maturation process and agro-climatic conditions. In the present work, the severe drought observed during the year 2017 (data not shown) probably promoted the synthesis of these antioxidants, perhaps as a protection of the plant against the increased environmental stress (Beltrán et al, 2005).…”
Section: Quality and Physicochemical Parameterssupporting
confidence: 88%
“…Tura et al, 2007). And, for Verdeal Transmontana and Redondal, are in the same order of the values obtained for the two most common cultivars in Portugal (Galega Vulgar and Cobrançosa) (Peres et al, 2016). The TP content seemed to be significantly influenced by olive cultivar (Pvalue < 0.0001), ranging from 75 to 135 mg CAE/kg of olive oil in 2016 and from 164 to 363 mg CAE/kg of olive oil in 2017, with the highest values consistently observed in cv.…”
Section: Quality and Physicochemical Parameterssupporting
confidence: 79%
See 1 more Smart Citation
“…Cobrançosa, with reported amounts of 99–313 mg/kg of olive oils, being these values dependent from the storage conditions of the olive fruits before extraction (Pereira et al, ), olive fly attack (Pereira et al, ), decreasing along the fruit ripening (Matos et al, ), and increasing with the addition of olive leaves during extraction (Malheiro et al, ). Also, Peres et al () reported that olive oils extracted from olives of cv. Cobrançosa and other typical cultivar (cv.…”
Section: Discussionmentioning
confidence: 99%
“…Olive fruits are very rich in phenolic compounds, with the exact composition depending on different variables, the more relevant of which are cultivar, climatic conditions and degree of maturation . Nevertheless, it is well known that only a minor part of this phenolic fraction passes in the olive oils during the extraction process, mainly depending on their predominant hydrophilic nature and the enzymatic activities .…”
Section: Introductionmentioning
confidence: 99%